2017
DOI: 10.1021/acs.est.6b05025
|View full text |Cite
|
Sign up to set email alerts
|

Cats’ Internal Exposure to Selected Brominated Flame Retardants and Organochlorines Correlated to House Dust and Cat Food

Abstract: Pet cats may be used as a biomarker for assessing exposures to organohalogen compounds (OHCs) adsorbed to household dust in home environments. This study explores two exposure routes of OHCs, ingestion of OHCs (i) via house dust and (ii) via cat food. House dust from 17 Swedish homes and serum from the participating families' pet cats were collected, and cat food was purchased matching the diet reported. Paired samples of cat serum, house dust, and cat food were analyzed for brominated flame retardants/natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 64 publications
6
38
0
Order By: Relevance
“…Currently, the only compound of the BDE family that is still approved for use is BDE-209 (), and it has to be taken into account that unfortunately this chemical was not included in this study, because it can not be determined in our laboratory due to technical limitations. In any case, and even without having included the BDE 209, our results are very similar to those reported in cats from Pakistan (median ∑BDEs = 6.1 ng/g fat) (29), USA—Georgia, Massachusetts, and North Carolina—(median ∑BDEs = 5.9 ng/g fat) (17), but lower than those reported in Sweden (median ∑BDEs = 24.1 ng/g fat) (34), and than in those cats from California, in which the authors reported extraordinarily high levels of BDEs (median ∑BDEs = 2904 ng/g fat), mainly due to the high levels of BDE-99 detected in those animals (19). While diet, mainly through fish intake, is considered the main route of exposure for PCBs (23, 3537), the ingestion of dust from the environment is considered the most important route of exposure for BDEs in cats (38).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Currently, the only compound of the BDE family that is still approved for use is BDE-209 (), and it has to be taken into account that unfortunately this chemical was not included in this study, because it can not be determined in our laboratory due to technical limitations. In any case, and even without having included the BDE 209, our results are very similar to those reported in cats from Pakistan (median ∑BDEs = 6.1 ng/g fat) (29), USA—Georgia, Massachusetts, and North Carolina—(median ∑BDEs = 5.9 ng/g fat) (17), but lower than those reported in Sweden (median ∑BDEs = 24.1 ng/g fat) (34), and than in those cats from California, in which the authors reported extraordinarily high levels of BDEs (median ∑BDEs = 2904 ng/g fat), mainly due to the high levels of BDE-99 detected in those animals (19). While diet, mainly through fish intake, is considered the main route of exposure for PCBs (23, 3537), the ingestion of dust from the environment is considered the most important route of exposure for BDEs in cats (38).…”
Section: Discussionsupporting
confidence: 86%
“…Thus, due to their grooming habits, cats have been classically used to evaluate the level of human exposure to BDEs through the indoor dust (39). In this sense, a positive correlation between serum cat levels and dust has been consistently reported in the literature (34), although the serum levels tend to be several times higher in cats than in humans. Compared to humans, ∑BDE levels in cats are often 20- to 100-fold greater than median levels in US adults (17, 38), but the correlation of levels and the pattern of contamination (congener distribution and proportions) between both species has been reported to be very good.…”
Section: Discussionmentioning
confidence: 52%
“…Humans and pets are ubiquitously exposed to various FRs, via diet, through direct contact with consumer products, and through household dust, which is used to measure indoor chemical contamination and to assess human exposure risks (Jones-Otazo et al, 2005;Whitehead et al, 2011). Children and indoor pet cats may, therefore, have greater exposures to FRs through dust ingestion than adults (Norrgran Engdahl et al, 2017). Since pet cats have previously been presented as a potential bio-sentinel for indoor pollution exposure, cats might therefore, have relevance as indoor exposure models for children (Dirtu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Ingestion of dust is considered an important exposure route to organic contaminants, including THDCs (Fromme et al, ; Hammel et al, ; Jones‐Otazo et al, ; Mercier, Glorennec, Thomas, & Le Bot, ; Norrgran Engdahl et al, ; Sahlström, Sellström, De Wit, Lignell, & Darnerud, ; Whitehead et al, ). Indoor dust contains a multitude of industrial chemicals originating from, e.g., furniture, textile, plastics and electronic products as reviewed by Lucattini et al ().…”
Section: Introductionmentioning
confidence: 99%